Crise financeira: o caso japonês - Fraga, Jefferson Souza [UNESP] (2013)
This paper aims to analyze the experience of Japan after the collapse of speculative bubbles in assets and the banking crisis in the 1990s. An analysis about the effectiveness of fiscal and monetary policy is conducted and the measures taken with respect to the banking sector are also discussed in this paper. The Japanese financial crisis experience suggests that the nature, speed and order in which the government implements measures determine, in large part, the magnitude and cost of the crisis. Therefore, in hindsight, it can be said that the following tasks were necessary: 1) recapitalize the banking sector; 2) restore credit; and 3) reinvigorate the economic activity through appropriate fiscal measures.